Which is More Influential? Internal Factors or External Factors of Banks on the Profitability of Conventional Banks - Juan Carlos; Sri Indah Nikensari; Siti Fatimah Zahra (Forum Kerjasama Pendidikan Tinggi, 2023)
This study looks at how macroeconomic variables such as inflation and exchange rates, as well as internal issues such as bad debts and loan-to-deposit ratio, affect bank profitability as determined by return on assets. Using the eviews 12.0 program, panel data regression is used as an analytical tool in this study. There are 47 banks in Indonesia listed on the Indonesia Stock Exchange between 2018 and 2022. The results concluded that External factors are factors that have a stronger influence on profitability because after testing simultaneously there are two significant variables, namely inflation and exchange rates and for internal factors only one variable, namely non-performing loans so that external factors are stronger on the profitability of conventional banks in the Indonesian Stock Exchange.